Rotavirus infection of the oropharynx and respiratory tract in young children - Zheng, B J; Chang, R X; Ma, G Z; Xie, J M; Liu, Q; Liang, X R; Ng, M H (Journal of medical virology, 1991)
Oropharyngeal aspirates were obtained from 89 infants hospitalized with respiratory illnesses accompanied or not by diarrhea and 33 control patients without the diseases. Rotavirus was detected from 25 of these patients by immunocytology, isolation of the virus in cultures of MA104 cells, or both. None of the control patients gave a positive result. The infection involves squamous cells and globlet cells probably originating from the oropharynx, and ciliated columnar epithelial cells from the respiratory tract. The virus from 2 specimens was propagated by repeatedly passaging in the cultures and found to have characteristic morphology of rotavirus. The electrophoretic patterns of the viral RNA extracted from them are closely similar to those obtained with the rotavirus genome extracted from the stool of the same patients. Repeated stool specimens were also obtained, and sera were paired from some of these subjects. All but one of the patients who gave a positive virology for their aspirates also showed a significant rise in the titres of common group A rotavirus antibody, neutralizing antibody against one or more of serotypes of rotavirus, or both. Patients who excreted rotavirus in their stools were younger and had significantly lower titres of rotavirus antibodies in their acute sera, than those who shedded the virus in the oropharynx but did not excrete the virus in repeated stool specimens. The prevalence of rotavirus in the oropharyngeal aspirates from these patients surpassed that of adenovirus, respiratory syncytial virus, influenza virus, and herpes simplex virus combined.